Design of Physical Exercises Adapted to Improve the Nursing Students Physical Activity in Cienfuegos - Lázaro Dionisio Rojas Matsuda; Isaac Rodríguez Palacios; Katia Rodríguez Palacios; Ivis Espinoza Requesén; Yasser Hernández Hernández (Revista Finlay)
Background: physical activity reduces the risk of obesity and is associated with mental health, emotional well-being and greater longevity. Nursing students at the Cienfuegos University of Medical Sciences have negative results regarding the physical activity level. Objective: to design a set of adapted physical exercises that allows improving the nursing student’s physical activity levels at the Cienfuegos University of Medical Sciences. Methods: a descriptive, retrospective, cross-sectional study was carried out in nursing students from the Cienfuegos University of Medical Sciences from January to December 2019. The universe consisted of 133 nursing students from 3rd to 5th year and the sample by sex; 15 females and 15 males, which represents the 25 % of the chosen population. Among the applied techniques were: the nominal group, the survey and the participant observation. Descriptive statistics were used to obtain data on means and percentages. Results: a proposal of physical exercises for different muscular planes was designed in an affordable way for the practitioners, consisting of practicing them three times a week with the required methodology. Conclusions: the design of physical exercises, turned out to be a methodological tool that responds to the need to develop the organic motor capacities in its dimensions: strength, speed, flexibility and resistance, using with creativity methods, techniques and strategies of physical activity to achieve a change in attitude to the growing sedentary lifestyle that affects the university population so much.